2019
DOI: 10.1002/bit.27130
|View full text |Cite
|
Sign up to set email alerts
|

Lichenicidin rational site‐directed mutagenesis library: A tool to generate bioengineered lantibiotics

Abstract: Lantibiotics are ribosomally synthesized and posttranslationally modified antimicrobial peptides that arise as an alternative to the traditional antibiotics. Lichenicidin is active against clinically relevant bacteria and it was the first lantibiotic to be fully produced in vivo in the Gram‐negative host Escherichia coli. Here, we present the results of a library of lichenicidin mutants, in which the mutations were generated based on the extensive bibliographical search available for other lantibiotics. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…For RiPPs assembled by promiscuous enzymes, combinatorial libraries can be generated and screened against a target of interest to discover new compounds with designer biological activities. Assessing whether a particular biosynthetic pathway is suitable for such purposes is usually a labor-intensive process because numerous mutants for each participating enzyme need to be analyzed. Contemporary mutagenesis approaches address this issue to some extent by enabling simultaneous profiling of dozens of compounds, but both in vivo and in vitro strategies mostly provide qualitative output with no temporal resolution. For instance, analysis of enzyme preferences from in vivo data may be confounded by metabolic stability of the mutants as well as by export, self-immunity, and associated issues.…”
mentioning
confidence: 99%
“…For RiPPs assembled by promiscuous enzymes, combinatorial libraries can be generated and screened against a target of interest to discover new compounds with designer biological activities. Assessing whether a particular biosynthetic pathway is suitable for such purposes is usually a labor-intensive process because numerous mutants for each participating enzyme need to be analyzed. Contemporary mutagenesis approaches address this issue to some extent by enabling simultaneous profiling of dozens of compounds, but both in vivo and in vitro strategies mostly provide qualitative output with no temporal resolution. For instance, analysis of enzyme preferences from in vivo data may be confounded by metabolic stability of the mutants as well as by export, self-immunity, and associated issues.…”
mentioning
confidence: 99%
“…When the "Lid" is opened, an electrophilic region will be formed around Ser to expose the hydrophobic residue, thus enhancing the affinity with the substrate to interact with the core catalytic amino acids. At the same time, the existence of the "Lid" maintains the stability of the intermediate product in the catalytic process [37][38][39][40]. The 3D structure showed that the overall structure of PlaS presented a slightly curved envelope shape.…”
Section: Discussionmentioning
confidence: 98%
“…Due to its distinctive mode of action, broad range of antimicrobial activity and its gene-encoded nature, nisin A is an obvious choice for genetic manipulation in a bid to enhance its functionality. Indeed, several recent bioengineering studies involving nisin and other lantibiotic peptides, including mutacin, mersacidin, lichenicidin, and nukacin ISK-1, have been successful in that regard as a consequence of the creation and screening of substantial banks of engineered peptides [24,[33][34][35]. In this study, we undertook the largest screen of such peptides to date involving approximately 30,000 nisin derivatives against several representative mastitis-associated pathogenic targets including staphylococci and streptococci.…”
Section: Discussionmentioning
confidence: 99%